Recent Developments and Strategies for the Application of Agrobacterium-Mediated Transformation of Apple Malus × domestica Borkh - Schröpfer, Susan; Lempe, Janne; Emeriewen, Ofere Francis; Flachowsky, Henryk (Frontiers in Plant Science, 2022)
Genetic transformation has become an important tool in plant genome research over the last three decades. This applies not only to model plants such as Arabidopsis thaliana but also increasingly to cultivated plants, where the establishment of transformation methods could still pose many problems. One of such plants is the apple (Malus spp.), the most important fruit of the temperate climate zone. Although the genetic transformation of apple using Agrobacterium tumefaciens has been possible since 1989, only a few research groups worldwide have successfully applied this technology, and efficiency remains poor. Nevertheless, there have been some developments, especially in recent years, which allowed for the expansion of the toolbox of breeders and breeding researchers. This review article attempts to summarize recent developments in the Agrobacterium-mediated transformation strategies of apple. In addition to the use of different tissues and media for transformation, agroinfiltration, as well as pre-transformation with a Baby boom transcription factor are notable successes that have improved transformation efficiency in apple. Further, we highlight targeted gene silencing applications. Besides the classical strategies of RNAi-based silencing by stable transformation with hairpin gene constructs, optimized protocols for virus-induced gene silencing (VIGS) and artificial micro RNAs (amiRNAs) have emerged as powerful technologies for silencing genes of interest. Success has also been achieved in establishing methods for targeted genome editing (GE). For example, it was recently possible for the first time to generate a homohistont GE line into which a biallelic mutation was specifically inserted in a target gene. In addition to these methods, which are primarily aimed at increasing transformation efficiency, improving the precision of genetic modification and reducing the time required, methods are also discussed in which genetically modified plants are used for breeding purposes. In particular, the current state of the rapid crop cycle breeding system and its applications will be presented.